Presenting a structural model of the relationship between perfectionism and life expectancy with the mediating role of moral intelligence and spiritual intelligence in the administrators of Islamic Azad University of Mazandaran province - Khosravi, Seyed Ahmad; Hosseinzadeh, Babak; Shojae, Ali Asghar; Sadeghi, Jamal (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Today, in today’s dynamic and risky world, in order to consolidate their survival, organizations must oblige their managers and employees to comply with ethical principles and acquire moral intelligence; Therefore, the purpose of this research was to present a structural model of the relationship between perfectionism and life expectancy with the mediating role of spiritual intelligence in the administrators of the Islamic Azad University of Mazandaran province. Methodology: In terms of purpose, this research was applied, and in terms of method, it was part of structural studies. Its statistical population consisted of all managers and deputy heads of units, heads and deputy heads of faculties, and heads of departments of Islamic Azad Universities of Mazandaran province, numbering 542 people. Based on Cochran’s formula, 225 people were selected as a statistical sample using stratified random sampling. Asadpour’s Perfectionism Questionnaire (2017), Schneider et al.’s Life Expectancy Questionnaire (1991), and King’s Spiritual Intelligence Questionnaire (2008) were used to collect data. Univariate regression tests and structural equations were used to analyze the data. Results: The results showed that the direct paths by the variables of perfectionism and spiritual intelligence have a direct and significant effect on life expectancy, and also, regarding the indirect path, the effect of perfectionism with the mediation of spiritual intelligence on life expectancy was confirmed. Conclusion: Considering the role of spiritual intelligence on life expectancy, it is necessary to plan in organizations to improve spiritual intelligence and identify and teach the destructive and adverse effects of perfectionism.